Sukarno, the Army, and the PKI during the Guided Democracy Era: A Complex Triangular Relationship - Israr, Israr; Anatona, Anatona; Midawati, Midawati (Analisis Sejarah, 2025)
This paper analyzes the dynamics of the triangle interaction of President Sukarno, the Indonesian Army, and the Communist Party of Indonesia during the Guided Democracy era, utilizing many new sources. The three predominant political entities that surfaced following the 1959 Presidential Decree not only offered political "direction" for that age but also illustrated a multifaceted triangle dynamic characterized by cooperation, competitiveness, and conflict. This research employs the four stages of the historical method to demonstrate that the political relationship among Sukarno, the Indonesian Army, and the Communist Party of Indonesia during the Guided Democracy era not only exhibited dynamic tensions but also culminated in the most catastrophic tragedy in the annals of independent Indonesia.